Effect of Distorted Visual Feedback on the Sense of Agency - C. Farrer; M. Bouchereau; M. Jeannerod; N. Franck (Behavioural Neurology)
It has been hypothesized that an internal model is involved in controlling and recognizing one’s own actions (action attribution). This results from a comparison process between the predicted sensory feedback of the action and its real sensory consequences. The aim of the present study is to distinguish the respective importance of two action parameters (time and direction) on such an attribution judgment.